Impact of rainwater harvesting structures on water table behavior and groundwater recharge in Parasai-Sindh watershed of Central India - Kumari, Reena; Singh, Ramesh; Singh, R.M.; Tewari, R.K.; Dhyani, S.K.; Dev, Inder; Sharma, Babloo; Singh, A.K. (Indian Journal of Agroforestry, 2020)
The open shallow dug wells, situated in unconfined aquifer, are the major source of irrigation throughout Bundelkhand region of Central India. These wells, due to dependence on perched water, are characterized by very low specific yield and unable to support for continuous operation of pumps to irrigate the agricultural fields in a single stretch. This warrants water harvesting to ensure quick recharge in wells and thereby facilitate irrigation and in turn crop productivity. Therefore, to improve the water resources in Parasai-Sindh watershed (1246 ha) about 1,00,000 cum, rainwater harvesting facility was created through 10 cost-effective structures during 2012 and 2013. Ensuing study is an attempt to analyze the impact of these rainwater harvesting structures on water table and groundwater recharge. Water table fluctuation (WTF) method was applied during pre and post intervention phases to quantify groundwater recharge and to analyze the fluctuation of water table in open shallow dug wells. The average increase in water column, during monsoon for pre and post intervention, was recorded as 3.54 and 5.98 m, respectively. Average water column has increased by 69 per cent during 2013 due to watershed interventions. Net groundwater recharge, during monsoon season for pre and post interventions scenario, was estimated at 53.7 and 92.3 mm, respectively, which is 71.8 per cent higher than pre intervention phase. Improved yield of open wells reduced rabi fallow by about 70 ha besides, ensuring irrigation water through dug wells to rabi crops predominantly wheat in entire treated area of the watershed. The study has proved the efficacy of rainwater harvesting for groundwater recharge in Bundelkhand region.